Brain efficacy evaluation method based on exhaled gas omics - YANG ZEJI; ZHOU JIAJUN; JIANG XIAOXIA; XU ZHENHUA; CAO CAIZHUO; WU HAO; LI XIAOTONG; WANG YAN; RUAN HUAQIANG (2024)
The invention discloses a brain efficacy evaluation method based on exhaled gas omics, which discovers that brain fatigue subjects can be effectively identified by detecting volatile organic compounds such as butene, pentene, 1, 3-butadiene, ethyl formate, butanol, n-butane, acrolein, acrylonitrile, propionitrile, furan, methyl octanoate and/or ethyl sulfide in exhaled gas for the first time, and the brain fatigue subjects can be effectively identified by detecting the volatile organic compounds such as butene, pentene, 1, 3-butadiene, ethyl formate, butanol, n-butane, acrolein, acrylonitrile, propionitrile, furan, methyl octanoate and/or ethyl sulfide in the exhaled gas. Compared with the prior art, the method has the advantages of good diagnosis efficiency, high accuracy, high sensitivity and high specificity, provides a rapid and non-invasive diagnosis method for the technical field of brain fatigue identification, and has a wide application prospect. 本发明公开了一种基于呼出气体组学的脑效能评估方法，本发明首次发现通过检测呼出气体中的挥发性有机化合物丁烯、戊烯